Early syphilis in patients treated in the Department of Dermatology at Jagiellonian University School of Medicine in Cracow in years 2006-2010 - Pastuszczak, Maciej; Jaworek, Andrzej K.; Spałkowska, Magdalena; Miziołek, Bartosz; Wojas-Pelc, Anna (Dermatology Review/Przegląd Dermatologiczny, 2012)
Introduction . Syphilis is a sexually transmitted disease (STD), caused by the spirochete Treponema pallidum . The disease occurs only in humans. In the course of syphilis several stages are distinguished, which reflect the gradual spread of bacteria in the organism. Variety of sexual practices (including anal and oral sex), and widespread empirical use of antibiotics, prescribed for reasons other than STD (e.g. upper respiratory tract infections) not having treponemicidal action, seem to lead to changes in the clinical course of syphilis and its characterization by sparse symptoms. Objective . The aim of this study was to analyse the clinical manifestation of secondary syphilis in patients treated in the Department of Dermatology at Jagiellonian University, School of Medicine in Cracow. Material and methods . Data obtained from 217 patients including those of sociodemographic status, sexual orientation and HIV infection were analysed. Results. The analysed group consisted of 23 women (10.6%) and 194 men (89.4%), of whom 107 declared they were homosexuals. In 153 patients due to the absence of clinical signs of infection early latent syphilis was diagnosed. The most common clinical symptom of secondary syphilis was macular rash (43.7%), followed by maculopapular changes on the palms and soles (36.8%), generalized lymphadenopathy (33.3%), syphilitic alopecia (21.8%), syphilitic angina (14.9%) and condylomata lata (6.9%). 58.2% of patients had only one clinical symptom of the disease. The most common signs of infection were generalized lymphadenopathy and maculopapular rash on the soles and palms (11.5%). Conclusions . It seems that in the past two decades the clinical manifestation of secondary syphilis has not changed significantly. However, in comparison to data available from the literature different incidence of individual symptoms of secondary syphilis was observed, which may be explained by locally contingent diversity of sexual practices, use of empiric antibiotic therapy for reasons other than sexually transmitted infections and different accessibility to health care.